2008
DOI: 10.1111/j.1751-1097.2007.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Visible Light on the Skin

Abstract: Electromagnetic radiation has vast and diverse effects on human skin. Although photobiologic studies of sunlight date back to Sir Isaac Newton in 1671, most available studies focus on the UV radiation part of the spectrum. The effects of visible light and infrared radiation have not been, until recently, clearly elucidated. The goal of this review is to highlight the effects of visible light on the skin. As a result of advances in the understanding of skin optics, and comprehensive studies regarding the absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
166
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(179 citation statements)
references
References 106 publications
5
166
0
8
Order By: Relevance
“…Hem UVA hem de UVB maruziyeti melanin sentezini uyararak geç baş-langıçlı bronzlaşmaya yol açabilir. Klinik deneyim ve literatürde mevcut bilgiler ışığında, fasiyal hiperpigmentasyondan korunmak için hem UVA hem de UVB koruyuculuğu olan geniş spektrumlu, en azından 30 SPF özelliği olan ve tercihen titanium dioksid ya da çinko oksid gibi fiziksel bariyerler içeren güneş koruyucular tercih edilmelidir (26)(27)(28) .…”
Section: Güneşten Koruyucu Kremlerunclassified
“…Hem UVA hem de UVB maruziyeti melanin sentezini uyararak geç baş-langıçlı bronzlaşmaya yol açabilir. Klinik deneyim ve literatürde mevcut bilgiler ışığında, fasiyal hiperpigmentasyondan korunmak için hem UVA hem de UVB koruyuculuğu olan geniş spektrumlu, en azından 30 SPF özelliği olan ve tercihen titanium dioksid ya da çinko oksid gibi fiziksel bariyerler içeren güneş koruyucular tercih edilmelidir (26)(27)(28) .…”
Section: Güneşten Koruyucu Kremlerunclassified
“…52,53 Redistribution and oxidation of pre-existing melanin cause immediate pigment darkening and occurs after low-dose UVA exposure and usually fades after 2 h. 53,54 After high doses of UVA exposure, persistent pigment darkening may develop, lasting up to 24 h. Both UVA and UVB exposure can cause melanin synthesis resulting in delayed tanning. Given clinical experience and available data, broad-spectrum UVA and UVB protective sunscreen with an SPF of at least 30 ideally including a physical block (e.g.…”
Section: Sunscreensmentioning
confidence: 99%
“…It was found that pigmentation occurred even without the presence of UV radiation. Other studies have shown that the exposure of normal skin to visible light can result in the induction of immediate pigmentation (immediate pigment darkening -IPD), immediate erythema and delayed tanning (DT) [22].…”
Section: Radiation and Its Interaction With Skinmentioning
confidence: 99%